A survey on tomato leaf grey spot in the two main production areas of Argentina led to the isolation of S. lycopersici 6 representatives, which were genetically diverse and differ in virulence - Franco, Mario Emilio Ernesto (2017)
Tomato gray leaf spot was first reported in Argentina in 1990. Since then, the disease has not only increased in endemicc areas , but also disseminated in other tomatogrowing areas. In a survey of plantas with typic symptoms of Tomato grey leaf spot disease we isolated 27 Stemphylium representatives representatives from the two main tomato-growing areas of Argentina . Cultural features such as sporulation, conidia morphometry among others revealed high variability between isolates, which was confirmed by Inter simple sequence repeat (ISSR)-PCR technique A molecular phylogenetic analysis comprising the Internal Transcribed Spacer (ITS) and the glyceraldehyde-3-phosphate dehydrogenase (gpd) gene partial sequences unambiguously identified all isolates as Stemphylium lycopersici. Based on disease severity on detached leaves, isolates were grouped in three cathegories high, medium and low virulent one. No correlation was found between phenotypic orgenotypic characters and the geographical origin of the isolates.